2012
DOI: 10.5455/jmp.20120410105457
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of metals in managing diabetes mellitus: a review

Abstract: Diabetes mellitus (DM) represents one of the greatest threats to modern global health. Diabetes mellitus is characterized by chronic elevation of blood glucose concentration as a consequence of decreased blood insulin levels or decreased action of insulin. In order to prevent or delay the onset of such complications, tight control of fasting and postprandial blood glucose levels is a central aspect of diabetes treatment. Development of new therapies that are able to improve glycemia management, cure diabetes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 118 publications
0
10
0
Order By: Relevance
“…Copper is essential for the production of enzyme in the body and plays an important role in biological electron transport [56,57]. Copper deficiency causes reduced energy production, abnormal glucose and cholesterol metabolism, and increased oxidative damage [58]. Copper complexes can act as anticancer, antiulcer, anticonvulsant, and antidiabetic agents [59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Copper is essential for the production of enzyme in the body and plays an important role in biological electron transport [56,57]. Copper deficiency causes reduced energy production, abnormal glucose and cholesterol metabolism, and increased oxidative damage [58]. Copper complexes can act as anticancer, antiulcer, anticonvulsant, and antidiabetic agents [59].…”
Section: Discussionmentioning
confidence: 99%
“…Manganese is an essential component of metalloenzymes and plays essential role in a number of physiologic processes as a constituent or activator of some enzymes which are essential for the metabolism of carbohydrate, cholesterol and amino acid [58]. Cobalt is an important nutritional trace element having therapeutic value in pharmacological doses.…”
Section: Minerals Play a Key Role In Maintaining Proper Function Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Several animal studies have reported that high levels of Mo interfere especially with copper metabolism in animals which in turn results in alteration of normal hematological profile (Kusum et al, 2010;Pandey et al, 2012b). Histopathological examination of testis revealed high proportion of degenerated seminiferous tubules, with marked attenuation of the lining epithelium and diminished spermatogenesis in molybdenum treated sheep (Haywood et al, 2004), bulls (Thomas and Moss, 1951), rats (Pandey and Jain, 2015) and rabbits (Bersenyi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these herbs have also been acknowledged for their mineral elements and proximate compositions; they have nutritional qualities that could provide the users with additional nutrients (Abolaji et al, 2007). In fact, therapeutic and prophylactic properties of some medicinal plant parts have been attributed to their nutritional value rather than their phytochemical constituents (Akpinar-Bayizit et al, 2012;Pandey et al, 2012).…”
Section: Introductionmentioning
confidence: 99%